Individual and contextual determinants of the duration of diarrhoeal episodes in preschool children: a longitudinal study in an urban setting - Santos, Carlos Antonio de Souza Teles; Genser, Bernd (Epidemiology and infection, 2012)
This study investigated individual and contextual factors associated with the duration of diarrhoeal episodes in 693 young children living in a large Brazilian city who were followed-up for at least 3 months. The outcome is analysed as a continuous variable, by means of a hierarchical conceptual model organizing the factors in meaningful blocks. A total of 2397 episodes were recorded (median duration 2 days, interquartile range 1-3 days). Low percentage of households connected to the sewerage system in the neighbourhood, low family purchasing power, high agglomeration, mother aged <19 years, low zinc content in child's diet, and episode severity were significantly associated with longer duration (0·26-0·69 days more). Purchasing power effect was largely mediated by environmental conditions, characteristics of the child, and hygienic behaviour. Environmental conditions acted as a possible effect modifier, enhancing the effect on duration of diarrhoea of the child not having being vaccinated against measles or breastfed for >6 months.
Published online: 19 May 2011
Gesehen am 20.06.2018